Lethal and sublethal effects of chlorantraniliprole on Spodoptera cosmioides (Lepidoptera: Noctuidae) - Lutz, Alejandra (2018)
BACKGROUND: Spodoptera cosmioides (Walker, 1858) population has increased in Bt soybean crops in Argentina. As there are no registered products for its control, the recommended insecticides for S. frugiperda are used. The aim of this study was therefore to determine the lethal concentration (LC) and sublethal effects of chlorantraniliprole on the biological and reproductive functions of S. cosmioides, an emerging soybean pest in Argentina.RESULTS: An ingestion toxicity bioassay showed that chlorantraniliprole was active against larvae of the second instar, and after 48 h exposure LC50 was 0.054 μg/ml H2O. In the study of sublethal effect, chlorantraniliprole induced changes in the life cycle of exposed S. cosmioides, which required more time to complete all stages of development (larval, pupal and adult stages). Pupal weight was also higher in larvae exposed to sublethal concentrations of chlorantraniliprole. Adult fecundity was decreased: the number of eggs laid by each adult female moth, as compared to control females, was two (LC15) and eight (LC30) times smaller.CONCLUSION: These results indicate that chlorantraniliprole has toxicity against S. cosmioides larvae. Sublethal effects on the biological and reproductive performance of this species can help optimize integrated pest management programs.